ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI UNTUK BERKARIER DI BIDANG PERPAJAKAN DENGAN PELUANG KARIER SEBAGAI VARIABEL MODERASI - Lia Indah Setyawati; Manggar Wulan Kusuma (LPPM STIE YKPN Yogyakarta, 2023)
This study aims to determine the effect of perception, motivation, tax knowledge, behavioral attitudes, and professional recognition on the interest of accounting study program students at several universities in Yogyakarta to have a career in the field of taxation. Independent variables consist of perception, motivation, knowledge of taxation, behavioral attitudes, and professional recognition and career interest as the dependent variable. The contribution in this study, namely the authors added a moderating variable in the form of career opportunities which aims to strengthen the influence of the independent variables on the dependent variable.The results showed that perceptions, motivation, knowledge of taxation, and behavioral attitudes had an influence on the interest of students of accounting study programs in Yogyakarta to have careers in the field of taxation. Meanwhile, professional recognition has no effect on career interest in taxation and career opportunities cannot strengthen the influence of the independent variable on the dependent variable.